Closed Traumatic Rupture of the Thenar Muscles From the Origin. Issue 3 (March 2015) - Nguyen, Jesse T.; Nguyen, Jenny L.; Wheatley, Michael J.; Nguyen, Tuan A.
<x xml:space="preserve">Abstract</x> Abstract Closed traumatic rupture of the thenar muscles is an unusual and rare injury. Traumatic musculotendinous injuries in the hand and wrist occur primarily from penetrating trauma. Only 2 such cases were identified in medical literature. We report a case of closed traumatic rupture of the thenar muscles in an otherwise healthy 33-year-old female nurse who sustained a hyperabduction injury of her right thumb and wrist during a daily occupational routine, resulting in complete avulsion of the right abductor pollicis brevis and opponens pollicis from their origins. After declining initial surgical management, the patient subsequently returned 6 months later reporting continued pain, paresthesias, and thenar deformation, and requested surgical intervention. On examination, she continued to exhibit weakness of thumb abduction and mild weakness with opposition. She was again offered an open carpal tunnel release with exploration of the thenar eminence and possible tendon transfer, although she adamantly refused any tendon transfer. An open right carpal tunnel release was performed with exploration and direct muscle repair through a lateral thenar incision. Primary muscular reattachment was accomplished by suturing the abductor pollicis brevis and opponens pollicis to the flexor retinaculum and the trapezium. Functional results 15 months after surgery were satisfactory with improvements in abduction and opposition of the thumb and restoration of the thenar contour. The chosen surgical technique for repair resulted in good functional outcome, while avoiding the need for tendon transfer.